An innovative randomized response model based on a customizable random tool - Ahmad M. Aboalkhair; Mohammad A. Zayed; Tamer Elbayoumi; Abdullah Alnefaie; Mahmaod Alrawad; Ahmed M. Elshehawey (PLoS ONE, 2025)
This paper suggests an innovative randomized response model utilizing customizable random tool. The suggested model offers a general framework for some previously pioneering randomized response models and generates new efficient models. Comparison of the efficiency between one of these newly generated models and other groundbreaking models through theoretical and numerical ways, demonstrates higher efficiency for the new generated model. Additionally, ethical considerations and privacy protection of the suggested model are examined.